The Effect of Problem Based Learning Model on Problem Solving Ability and Mathematical Disposition - Yulia, Novi Ayu; Hendricks, Winston (Tematik : Jurnal Konten Pendidikan Matematika, 2024)
This research aims to determine whether there is a significant influence by applying the problem based learning model on the problem solving abilities and mathematical disposition of class XI students at SMA Negeri 1 Kraksaan. This research uses a quasi-experimental type of research with a pretest - posttest control group design. The population in this study was all class XI with a total of 245 students. Sampling used a cluster random sampling technique, and class XI.1 was selected as the experimental class and XI.2 as the control class. Research data was obtained from the results of learning implementation observation sheet instruments, problem solving ability test instruments, and mathematical disposition questionnaire instruments. Then the research data was analyzed using descriptive statistical analysis and inferential statistical analysis. The results of the hypothesis test show that the significant value obtained for problem solving ability is 0.000, so that H0 is rejected and H1 is accepted, which means that there is a significant influence using the problem based learning model on students' problem solving abilities at SMA Negeri 1 Kraksaan. Likewise, the results of the hypothesis test for the student mathematical disposition questionnaire showed a significance value of 0.000, so that H0 was rejected and H1 was accepted, which means that there is a significant influence using the problem based learning model on the mathematical disposition of students at SMA Negeri 1 Kraksaan.